Developing sport expertise: Researchers and coaches put theory into practice (Routledge, 2013)
The development of an athlete from basic performance to elite level of accomplishment is a long and complicated process. Identifying and nurturing talent, developing and fine tuning sport skills, and maintaining high levels of performance over the course of a career requires many thousands of hours of training and, increasingly, the input and support of expert coaches and sport scientists.